Psychogenic provocation of exacerbation of plaque psoriasis - Matiushenko Валерія (Psychosomatic Medicine and General Practice, 2018)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the psychogenic provocation of exacerbation of plaque psoriasis.